The Pórtico del Paraíso´ as Recipient of Foreign Artistic Models: Art, Power, Liturgy - Conde Cid, Natalia (Eikón / Imago, 2012)
The lack of enough medieval records difficults achieving a detailed study on the ‘Portico del Paraiso’ of the Cathedral of Ourense (Galicia). The present paper deals with that problem using the most reliable source, the building itself, in combination with the iconography of similar monuments.